CURRENT TRENDS IN SPORTS IN THE UAE - Salamatov, M.B.; Salamatova, K.G. (Theory and Practice of Physical Culture, 2023)
The development of sports on the world stage in the modern world has its own characteristics. Significant development of sports culture in general can be seen in the United Arab Emirates, in particular in Dubai. The global interest of the audience at the local and international levels is visible. Sport has literally changed the landscape of Dubai and created new landmarks, new opportunities on a global scale. Dubai is a city of action, and there is a huge variety of events that sports fans can participate in every week of the year. The UAE is interested in creating training centers throughout the country and investing resources in the construction of many modern sports facilities, as they realize the importance of these events for the development of the nation as a whole. The far-sighted approach of key stakeholders in the region is already yielding the first results, which are expressed in an increase in interest in sports events among the population, as well as an increase in representation among women athletes both at the national and global levels. The main organization for the development of physical culture and sports in the UAE is the Dubai Sports Council. Main trends: growing interest in sports, supporters of sports in Dubai, the future of sports culture in Dubai, facts and figures about sports in Dubai on the example of Dubai Pulse and other events, the emergence of more new sports, sandboarding, the introduction of additional sports federations in Dubai, additional committees.